2010
DOI: 10.1007/s00421-010-1718-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, inflammation and recovery of muscle function after damaging exercise: effect of 6-week mixed antioxidant supplementation

Abstract: There is no consensus regarding the effects of mixed antioxidant vitamin C and/or vitamin E supplementation on oxidative stress responses to exercise and restoration of muscle function. Thirty-eight men were randomly assigned to receive either placebo group (n = 18) or mixed antioxidant (primarily vitamin C & E) supplements (n = 20) in a double-blind manner. After 6 weeks, participants performed 90 min of intermittent shuttle-running. Peak isometric torque of the knee flexors/extensors and range of motion at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 58 publications
3
50
0
5
Order By: Relevance
“…Sputum neutrophil elastase was measured using an in-house continuous activity assay [21]. Sputum and urinary 8-isoprostanes were measured using an AutoDELFIA assay (PerkinElmer, Cambridge, UK) [22].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Sputum neutrophil elastase was measured using an in-house continuous activity assay [21]. Sputum and urinary 8-isoprostanes were measured using an AutoDELFIA assay (PerkinElmer, Cambridge, UK) [22].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Indeed, several studies have indicated that antioxidant supplementation induces a positive effect (1, 2), a negative effect (3,4), or no effect (5, 6) on muscle performance. Likewise, several studies have reported that antioxidant supplementation attenuates oxidative stress (7)(8)(9), others have reported that it induces a prooxidant effect (10)(11)(12)(13), and others have reported that it does not affect redox status (5,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…74,75 Bunun yanı sıra Close ve ark., iki haftalık C vitamini uygulamasının yokuş aşağı koşularda GKA düzeyinden bağımsız olarak oksidatif stres düzeyini azalttığını saptamışlardır. 76 Thompson ve ark., yokuş aşağı koşu sırasında oluşan kas hasarı biyo-işaretlerinin uzun süre C vitamini kullanan grupta ve plasebo grubunda benzer olduğunu, aynı zamanda C vitamini kullanımının IL-6 oluşumuna etkisi olmadığını belirlemişlerdir.…”
Section: Geci̇kmi̇ş Kas Ağrisi Ve Anti̇oksi̇dan Kullanimiunclassified